PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPAS MENGGUNAKAN MODEL TEAMS GAMES TOURNAMENTS (TGT) BERBANTUAN FLIPCARD DI KELAS IV SDN 15 ULU GADUT KOTA PADANG - Rulfani, Amelia Reski; Hamimah; Erita, Yeni; Amsari, Dina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The findings reveal that students are still experiencing poor educational results. This issue arises from insufficient student engagements in educational activities, as the teaching process remains largely led by the instructor. This study aimed to describe the improvement of learning outcomes in the IPAS subject through the implementation of the cooperative learning model, specifically the Teams Games Tournament (TGT) type, in grade IV of SDN 15 Ulu Gadut, Padang City. This research employed Classroom Action Research (CAR) by combining qualitative and quantitative approaches, conducted in two cycles. Each cycle consisted of planning, implementation, observation, and reflection stages. The subjects of this study were 25 students, consisting of 15 males and 10 females. Data were collected through observation techniques as well as test and non-test instruments to measure the effectiveness of the model. The evaluation results showed significant improvements in various aspects of learning. The quality of lesson module preparation increased from an average of 89.06% in the first cycle to 96.87% (very good) in the second cycle. Teacher activities in classroom management and student participation also improved consistently, from an average of 83.92% to 96.42% at the end of the second cycle. Learning outcomes covering attitudes, knowledge, and skills increased from an average score of 76.02 to 86.31 (good). These findings indicate that the use of the TGT model supported by flipcard media is highly effective in enhancing students’ interest and active participation, as well as improving their academic learning outcomes.